MARKOV SWITCHING AND THE TAYLOR PRINCIPLE. (12th May 2014) - Murray, Christian J.; Nikolsko-Rzhevskyy, Alex; Papell, David H.; Kim, Chang-Jin; Morley, James; Piger, Jeremy
<x content-type="archive" xml:space="preserve">Abstract</x> Early research on the Taylor rule typically divided the data exogenously into pre-Volcker and Volcker–Greenspan subsamples. We contribute to the recent trend of endogenizing changes in monetary policy by estimating a real-time forward-looking Taylor rule with endogenous Markov switching coefficients and variance. The response of the interest rate to inflation is regime-dependent, with the pre- and post-Volcker samples containing monetary regimes where the Fed did and did not follow the Taylor principle. Although the Fed consistently adhered to the Taylor principle before 1973 and after 1984, it followed the Taylor principle from 1975 to 1979 and did not follow the Taylor principle from 1980 to 1984. We also find that the Fed only responded to real economic activity during the states in which the Taylor principle held. Our results are consistent with the idea that exogenously dividing postwar monetary policy into pre- and post-Volcker samples is misleading. The greatest qualitative difference between our results and recent research employing time-varying parameters is that we find that the Fed did not adhere to the Taylor principle during most of Paul Volcker's tenure, a finding that accords with the historical record of monetary policy.